Product Quality, Price Perception, Green Packaging on Customer Satisfaction and Repurchase Intention Based on Sustainability - Amy Damayanti; Andyan Pradipta Utama (ARE Publisher, 2026)
Objective: This study aims to analyze the influence of customer satisfaction on product quality and price on repurchase intention. The population of this study was Holland Bakery customers inJakarta. Methodology: The sample in this study was 160 customers of Holland Bakery in Jakarta. The data analysis method used was Structural Partial Least Squares-Equation Model (PLS-SEM). Findings: The results of the study show that product quality and price perception influence customer satisfaction (Agneset al.,2025) and (Muthi & Utama, 2023) but product quality does not affect repurchase interest (Rahmawan & Irmawati, 2024) and (Azizet al., 2023). Green packagingdoes not affect customer satisfaction but does affect repurchase intention (Arianty & Ariska, 2023). Customer satisfaction influences repurchase intention (Kotler & Keller, 2022). Customer satisfaction can mediate the influence of product quality and price perception by full mediation (Kartikaet al., 2023) and (Muthi & Utama, 2023), however customer satisfaction is not able to mediate the influencegreen packagingon repurchase intention. Conclusion: Product quality and price perception have a positive and significant effect on customer satisfaction, but green packaging does not have a significant effect on customer satisfaction. Meanwhile, product quality and price perception do not have a significant effect on repurchase intention, but green packaging and customer satisfaction have a positive and significant effect on repurchase intention. Customer satisfaction is able to mediate the influence of product quality and price perception on repurchase intention positively and significantly, but customer satisfaction is not able to mediate the influence between green packaging on repurchase intention.